The adoption of automation in Schenker Penang Logistics Centre 5 (plc5) warehouse: A case study - Chuah, Yu Ru; Goh, Ai Vin; Ooi, Hui Tian (2023)
Warehouse automation is one of the technologies implemented in Industry 4.0 and has greatly benefited various industries by increasing productivity, effectiveness, and efficiency in warehouse operations. These technologies have been adopted in most foreign countries, such as Germany, the United Kingdom, and China. Therefore, Malaysia has yet to urge or advise stepping into warehouse automation in the available industry sector. This study was carried out at Penang Logistics Centre 5 (PLC5), Schenker Logistics (M) Sdn. Bhd., to discuss the relationship between advanced technologies and the current warehouse operation in solving the issues that arose. Meanwhile, the data collection process will be done by conducting physical and virtual interviews with middle-level management to obtain the facts necessary to access the current warehouse operations, identify the complications that arise from these operations, and propose appropriate technology to enhance the current operation. Besides, thematic analysis has been used to analyse the data, and the findings obtained are believed to be very legible and usable for PLC5, Schenker Logistics (M) Sdn. Bhd. in future warehouse operations.